When calls the heart [large type] - Oke, Janette, 1935- (Oke, Janette, 1935- Canadian West series, 2011)
Nothing in her cultured Eastern upbringing prepared Elizabeth for a teaching position in the Canadian West; even though she cares for the children, she is determined not to open her heart to the local frontiersmen until she meets a member of the Royal Canadian Mounted Police.